Rankings and the reshaping of higher education : the battle for world-class excellence - Hazelkorn, Ellen (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'University rankings have gained popularity around the world, and are now a significant factor shaping reputation. This book is the first comprehensive study of rankings from a global perspective, making an important contribution to our understanding of the rankings phenomenon'--
Includes bibliographical references and index
Keywords: Education, Higher -- Evaluation -- Cross-cultural studies; Universities and colleges -- Evaluation -- Cross-cultural studies; Higher education and state -- Cross-cultural studies; Globalization